2000
DOI: 10.1021/ed077p1581
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sugar-chlorate rocket demonstration

Abstract: The sucrose and potassium chlorate demonstration has been modified to provide a safer ignition method and to increase its spectacular nature. Ignition is best accomplished by placing a safety match head in the mixture and igniting the safety match with a butane lighter of the type used for outdoor grills. A brilliant rocketlike flame can be produced by carrying out the reaction in a short piece of capped plumbing pipe. The plumbing pipe is concealed in a sand bath, which has the advantages of limiting any sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…49 In this experiment, we made rockets using sugar as the main fuel source, demonstrating the highly oxidizable nature of sugar. 50 To make these rockets, the participants combined sugar and potassium nitrate, and packed the mixture into a plastic tube with kitty litter at both ends. Inserting a fuse, mounting the rocket on a launcher, and igniting the fuse completed the activity and allowed for successful rocket launches by nearly all program participants.…”
Section: Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In this experiment, we made rockets using sugar as the main fuel source, demonstrating the highly oxidizable nature of sugar. 50 To make these rockets, the participants combined sugar and potassium nitrate, and packed the mixture into a plastic tube with kitty litter at both ends. Inserting a fuse, mounting the rocket on a launcher, and igniting the fuse completed the activity and allowed for successful rocket launches by nearly all program participants.…”
Section: Activitiesmentioning
confidence: 99%
“…Many different chemicals can be used as rocket fuel, including gunpowder, alcohol, and kerosene . In this experiment, we made rockets using sugar as the main fuel source, demonstrating the highly oxidizable nature of sugar . To make these rockets, the participants combined sugar and potassium nitrate, and packed the mixture into a plastic tube with kitty litter at both ends.…”
Section: Program Informationmentioning
confidence: 99%
“…The literature presents various formulations to make bengal lights (6 ), but frequently those mixtures do not give spectacular results. Recently, Eliason et al (7 ) suggested the well-known sucrose-potassium chlorate mixture as a "basic composition". A new efficient basic composition has been obtained with potassium chlorate and thiourea.…”
Section: Risk Of Explosionmentioning
confidence: 99%
“…G. W. Eastland had previously used thermite to ignite such a KClO 3 mixture for effect . Indeed, the KClO 3 reaction itself has been used to great effect in its own right as a tool for demonstrating reaction dynamics …”
Section: Introductionmentioning
confidence: 99%